HUMAN ORGAN TRANSPLANTATION: LEGAL SYSTEM MONITORING - Yanchuk, А.О.; Kuznichenko, S.О.; Gradova, Yu.V. (World of Medicine and Biology, 2018)
The study focuses on human organ transplantation that is a significant issue in medical law. The paper presents the overview of the international and national legislation in the field of human organ transplantation. The new Law of Ukraine “On human anatomical transplantation” has been analyzed.
Keywords: organ transplantation; transplantology; donor; recipient; human organ trafficking; anatomical material; medical law